HUBUNGAN RUTINITAS SALAT DHUHA DENGAN PREVALENSI LOW BACK PAIN PADA MUSLIMAH LANSIA - AINUN ULFAH SA’ADIAH HARAHAP; ELMAN BOY (JURNAL ILMIAH MAKSITEK, 2021)
Low back pain (LBP) occurs due to the wrong ergonomics of body posture, causing musculoskeletal disorders withmanifestations of pain that can lead to disability. LBP commonly occur in elderly. Dhuha prayer which is held in the morning,is optimal as a light-moderate physical activity. The movements performed during the Dhuha prayer can act as stretchingexercises due to non-pharmacological treatment of low back pain. This study is quantitative study, using a cross-sectionalstudy design. This research was conducted in December 2020 at the Panti Sosial Tresna Werdha Abadi, Binjai City, with atotal sample of 30 people who were taken using total sampling technique. Data analysis was performed using SPSS with theSpearman analysis test. RESULTS: the research results obtained data of the value of Sig. (2-tailed) 0.021 and thecorrelation coefficient (r) 0.421. There is a relationship between the Dhuha prayer routine and the prevalence of LBP inelderly Muslim women.